AMLODIPINE IN TREATMENT OF PATIENTS WITH CORONARY ARTERY DISEASE: FOCUS ON ANTIATHEROSCLEROTIC PROPERTIES - Yu. M. Lopatin (Столичная издательская компания, 2016)
Author discusses antiatherosclerotic effects of dihydropyridine calcium channel blocker, amlodipine, in patients with coronary artery disease. Results of randomized clinical trials PREVENT (2000), CAPARES (2000), CAMELOT (2004) and ENCORE II (2009) are analyzed.